THE EFFECTIVENESS OF PROBLEM-BASED LEARNING MODEL TOWARD THE ABILITY OF CONCEPT COMPREHENSION AND STUDENTS CREATIVITIENESS IN SMP N 3 JETIS - Sinta Dewi Purwati; Uswatun Khasanah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
The mathematics learning at SMP N 3 Jetis Bantul is still using a direct instructional model. In this model, the teacher plays an important role in providing information about new concepts and demonstrate a pattern or rules. It makes the process of concept comprehension and creativity of students is very low. The study aimed to know the differences between the ability of concept comprehension and students’ creativity in the learning which was using problem-based learning models and direct instructional model along compared to the effectiveness of both models toward the ability of concept comprehension and student’s creativity. There are four classes of research subjects, they are VIII D, VIII E, VIII F, and VIII G SMP N 3 Jetis Bantul. The researcher used a purposive sampling technique class VIII G chosen as an experimental class and VIII F as a control class. The design of the research was posttest only control design. Data collection technique used to test. Data collection instruments such as concept comprehension in the form of posttest essay questions and essay questions creativity. Test data collection instruments used validity test and reliability test. The Data analysis technique used was the prerequisites test analysis including normality test and homogeneity test continued hypothesis test.  The results of experimental class hypothesis test with significance level 5% and showed that: (1)  so  then there was a significant difference between the ability of concept comprehension which used problem-based learning model and direct instructional model (2) so  then there was a significant difference of student creativity which used problem-based learning model and direct instructional model, (3)   so  then the results of students mathematics learning used problem-based learning model was better than using direct instructional model, (4)  so  then student creativity who used problem-based learning model was better than using the direct instructional model.